(untitled) (Marketing Journal, 2025)
This article analyzes theoretical aspects of long -term assets in accounting. It presents various approaches and forms of representation of such assets in regulatory documents, including shares, bonuses, and resources acquired by enterprises for long - term u se. Long -term financial investments and assets recognized as investment property are also considered as effective directions for future capital allocation. Therefore, revisiting the classification and characteristics of long -term assets is of significant r elevance.